Proses Analog Switch-Off Menuju Televisi Digital (Studi Kebijakan Penyiaran Televisi Digital di Indonesia) - Sinambela, Samuel Septuadi; Dwianna, Ressi; Rahma, An Nisa Dian (Universitas Medan Area, 2024)
In Indonesia, television has gone through the Analog Switch-Off (ASO) phase, switching from analog to digital broadcasting. In response, research was conducted to understand the digitalization policy of television in Indonesia. This research uses qualitative methods with a descriptive approach, combining documentation, observation, and interviews with two resource persons. The results showed that the process of digitizing television in Indonesia was slow and filled with obstacles, especially related to unclear policies and regulations. The lack of clarity in policies results in losses for people who experience limited access to television as a medium of public communication and source of information. Therefore, the government needs to formulate detailed policies to ensure that television digitalization does not harm society. This is important because television is one of the main means of communication and information of society.